Design Conformity of Indonesian-Made Mini Rice Combine Harvester and Anthropometry of Javanese Farmers - Guntarti Tatik Mulyati; Muhammad Maksum; Bambang Purwantana; Makhmudun Ainuri (agriTECH, 2020)
The combine harvester in Yogyakarta Province Special Region has a small size because it is used to harvest rice in a narrow area. The purpose of this study is to determine which parts of the mini combine harvester machine are not ergonomic and need to be improved so that the operator can work comfortably and safely. The types of mini combine harvester machines investigated in this study are QUICK H140R, TANIKAYA Ironbee HT12, and JAP001. Results showed that, for the three combine harvester machines, there was a mismatch in the physical size of the engine and the anthropometry of the operator. The main problems of the mini combine harvester machine are less ergonomic seat, inappropriate placement of the control table, hand activity in the maximum area, narrow workspace for leg movements, and less supportive footstep for the operator to work while standing. This information is expected to be utilized by Indonesian mini combine harvester machine designers so that the new design of combine harvester machines will be ergonomic, safe, and comfortable.